2020
DOI: 10.1177/2165143420948838
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Matter: The Role Transition Specialists Play in Youth’s Reentry From the Juvenile Justice System

Abstract: Increasing engagement to school, employment, and community are strong predictors of reducing recidivism for youth involved in the juvenile justice system. This study examined what occurs at reentry upon leaving a youth correctional setting. This study comprised of qualitative semi-structured interviews of transition specialists (TSs; n = 7) and young offenders ( n = 8) who participated in a 4-year reentry project in the Pacific Northwest. A total of 21 (13 TS and eight youth) interviews were thematically coded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 23 publications
(31 reference statements)
0
19
0
Order By: Relevance
“…Five studies related to Principle V met selection criteria. With regard to participants, four of the five studies addressed youth with special needs (Mathur et al, 2020, 2021; Ruch & Yoder, 2018; Sinclair et al, 2020). These studies included 7,231 youth, seven transition specialists, and 98 employers as their participants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five studies related to Principle V met selection criteria. With regard to participants, four of the five studies addressed youth with special needs (Mathur et al, 2020, 2021; Ruch & Yoder, 2018; Sinclair et al, 2020). These studies included 7,231 youth, seven transition specialists, and 98 employers as their participants.…”
Section: Resultsmentioning
confidence: 99%
“…One study identified learning disability as the only category for special needs (Ruch & Yoder, 2018), and two identified LD, emotional disabilities, and other disabilities as primary categories for special needs (Mathur et al, 2020, 2021). One study (Sinclair et al, 2020) did not specify the type of special needs and only described their participants as receiving Individual Education Program (IEP) services. Four studies reported student race (Mathur et al, 2020, 2021, Ruch & Yoder, 2018; Sinclair et al, 2020) indicating that 2,002 youth were White, 2,349 were Black, 2,089 were Hispanic, and 791 were other.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ideally, as youths move between various schooling systems, in and out of JJ centers, their education plans and programs should build upon previous achievements to support continuity (Mathur & Griller Clark, 2013;Platt et al, 2015). Recent research conducted in the US has shown positive effects on re-engagement with education when transition back to the community is supported by evidence-based transition planning and processes (Griller Clark & Unruh, 2010;Hirschfield, 2014;Mathur & Griller Clark, 2013;Unruh, et al, 2019). Most youths, however, do not return to formal education post-release due to exclusionary policies, or if they do, they do not remain for long (Feierman et al, 2009).…”
Section: Introductionmentioning
confidence: 99%